Glucose Induces IL-1α-Dependent Inflammation and Extracellular Matrix Proteins Expression and Deposition in Renal Tubular Epithelial Cells in Diabetic Kidney Disease - Salti, Talal; Khazim, Khaled; Haddad, Rami; Campisi-Pinto, Salvatore; Bar-Sela, Gil; Cohen, Idan (Frontiers in Immunology, 2020)
Diabetes mellitus is linked with metabolic stress that induces cellular damage and can provoke renal inflammation and fibrotic responses that eventually lead to chronic kidney disease. Since the inflammasome-Interleukine-1(IL-1) IL-1α/IL-β-IL-1R are central elements of kidney inflammation and pharmacological IL-1R antagonist was shown to prevent or even reverse diabetic nephropathy (DN) in animal models, we explored the intrinsic expression of IL-1 molecules in kidney tissue of DN patients as regulators of renal inflammation. We used biopsies taken from DN patients and controls and show a high level of IL-1α expression in renal tubular epithelial cells while both IL-1 agonistic molecules (i.e., IL-1α and IL-1β) were devoid of the glomeruli. Human proximal tubular kidney HK-2 cells exposed to high glucose (HG), gradually increase the expression of IL-1α but not IL-1β and induce the expression and deposition of extracellular matrix (ECM) proteins. We further demonstrate that ectopic addition of recombinant IL-1α in low glucose concentration leads to a similar effect as in HG while supplementing excess amounts of IL-1Ra in HG significantly attenuates the ECM proteins overexpression and deposition. Accordingly, Inhibition of IL-1α cleaving protease Calpain, but not Caspapse-1, also strongly reduce ECM protein production by HK-2 cells. Collectively, we demonstrate that IL-1α released from renal tubular cells is the key inflammatory molecule responsible for the renal inflammation in DN. Our result suggests that the clinical use of IL-1Ra in DN should be promoted over the individual neutralization of IL-1α or IL-1β in order to achieve better blocking of IL-1R signaling.